Análise espaço-temporal dos casos de chikungunya no Espírito Santo entre 2018 e 2020: um estudo dos fatores associados - Clipes, Marcus Vinícius Salvador (2023)
Introdução: Chikungunya (CHIK) is a febrile illness caused by the Chikungunya virus (CHIKV), a global-wide distributed Alphavirus. The transmission of CHIKV occurs by the bites of female Aedes vector mosquitoes. CHIK was first evidenced and identified in 1953 in Tanzania. In Brazil, there have been autochthonous cases reported since 2014. Clinically, CHIK manifests itself by intense and sudden fever, followed by fatigue, headache, skin rash, and arthralgia, which can last for weeks to months, with consequences regarding public health and the quality of life for those affected. Although mortality is low, there are substantial morbid effects related to the disease. An understanding of the social and environmental determinants related to CHIK is crucial to establish disease control and mitigation strategies. Objective: This study aims to describe the social and demographic characteristics of individuals affected by Chikungunya (CHIK) in Espírito Santo state, evaluating their association with the disease incidence. Methods: We performed a cross-sectional study to describe temporal, spatial, and sociodemographic data of individuals with a confirmed diagnosis of CHIK in Espírito Santo state, Brazil, from 2018 to 2020. The analysis included monthly incidence calculation. The data processing regarding the annual spatial distribution resulted in the construction of maps disclosing the relative risks by each municipality and the distribution of clusters. Statistical analysis through the chi-square test indicated associations between sex, race, education, and age with the disease occurrence. Results: During the period and through the area analyzed, a CHIK epidemic occurred in 2020, with 2,198.2 cases per million inhabitants incidence. Southern and central regions harbored a risk five times higher than the others in the epidemic region. Women (odds ratio - OR 1.65; 95% Confidence Interval - CI 1.58- 1.72), afro descendants (OR 1.22; 95% CI 1.13-1.33), individuals with less than 11 years of education (OR 1.48; 95% CI 1.37-1.61), and elders (OR 7.49; 95% CI 6.53- 8.59) had the highest risk for the disease occurrence, a difference statistically significant. Conclusion: CHIK stands as an emerging public health problem in Brazil since its introduction in 2014. The population susceptibility and the broad vector distribution facilitate the virus dispersion through the country’s territory. Espírito Santo suffered a substantial epidemic in 2020, possibly related to outbreaks in neighboring 12 states. The population under risk should be prioritized in health care, considering the morbidity potential of the disease.